2005
DOI: 10.7326/0003-4819-143-10-200511150-00006
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in the Incidence of Venous Thromboembolism during Pregnancy or Postpartum: A 30-Year Population-Based Study

Abstract: Among pregnant women, the highest risk period for venous thromboembolism and pulmonary embolism in particular is during the postpartum period. Any prophylaxis against these events should be particularly targeted to postpartum women. Although the incidence of pulmonary embolism has decreased over time, the incidence of deep venous thrombosis remains unchanged, indicating the need to better identify pregnant women at increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
624
5
44

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,211 publications
(699 citation statements)
references
References 33 publications
26
624
5
44
Order By: Relevance
“…In a Singaporean study examining the psychosocial consequences of confinement practices, Chee et al (2005) found that a negative confinement experience was associated with depression. It is also recognised that the behavioural restrictions and reduced mobility enforced during the confinement period places women at increased risk for development of venous thromboembolism (Heit et al, 2005). Steinberg (1996) suggests research is needed to identify those practices, which are unsafe and potentially harmful, thus ought to be discouraged, as well as those which enrich the experience of childbearing and should be retained.…”
Section: Changing Practicesmentioning
confidence: 99%
“…In a Singaporean study examining the psychosocial consequences of confinement practices, Chee et al (2005) found that a negative confinement experience was associated with depression. It is also recognised that the behavioural restrictions and reduced mobility enforced during the confinement period places women at increased risk for development of venous thromboembolism (Heit et al, 2005). Steinberg (1996) suggests research is needed to identify those practices, which are unsafe and potentially harmful, thus ought to be discouraged, as well as those which enrich the experience of childbearing and should be retained.…”
Section: Changing Practicesmentioning
confidence: 99%
“…The risk of venous thromboembolism (VTE) is five times higher in pregnant than in non-pregnant women [1,2]. The incidence of pregnancy-associated VTE varies from 1 in 1000 to 1 in 2000 deliveries [3].…”
Section: Introductionmentioning
confidence: 99%
“…If LMWH increases the risk of major haemorrhage by 1/200, then for every PE death avoided with LMWH, more than 1000 women experience major haemorrhage. Although an apparent drop in PE deaths in the UK from 2003 to 2008 has been attributed to increased VTE prophylaxis, newer data show no sustained decrease 21, 56, 57. The incidence of fatal PE during 3‐year time periods ending in 2002, 2005, 2008 and 2011 were 1.5, 1.94, 0.79 and 1.26 per 100 000 births 58.…”
Section: Death From Pulmonary Embolismmentioning
confidence: 99%